Reconceptualising Museum Pedagogy in Informal Learning Contexts:A Systematic Literature Review - Vitari, Aulia; Hariri, Hasan; Sinaga, Risma Margaretha; Sunyono (Universitas Islam Negeri Raden Intan Lampung, 2026)
Museums have progressively evolved from static repositories of cultural heritage into dynamic, learner-centred educational institutions that support informal, lifelong, and socially situated learning. This study aimed to systematically synthesise contemporary research on museum pedagogy in order to identify dominant theoretical orientations, pedagogical practices, and emergent challenges across diverse museum learning contexts. Employing a systematic literature review (SLR) design in accordance with the PRISMA 2020 guidelines, the study analysed 18 peer-reviewed articles published between 2020 and 2025 in journals indexed in Scopus, Web of Science, and SINTA 1–2. Thematic synthesis, supported by independent coding with an inter-rater reliability coefficient of κ = 0.82, was applied to examine patterns across the literature. The analysis identified six interrelated dimensions of contemporary museum pedagogy: (1) technology-enhanced museum learning, (2) experiential and constructivist approaches, (3) inclusive and accessible pedagogical practices, (4) cross-curricular integration, (5) visitor engagement and meaning-making, and (6) professional development of museum educators. The findings indicate a conceptual shift from isolated educational activities toward coherent pedagogical designs that integrate digital mediation, sociocultural participation, and inclusive learning principles. Persistent gaps remain in longitudinal assessment of learning outcomes, cross-cultural comparative research, and empirical operationalisation of inclusive pedagogical frameworks. This study contributes an integrative synthesis that advances theoretical coherence in museum pedagogy and provides evidence-based insights for researchers, museum practitioners, and policymakers seeking to design inclusive, pedagogically grounded, and digitally responsive museum learning environments.